Las familias monoparentales y su incidencia en el desarrollo social de los niños y niñas de primer año de educación básica de la escuela José Ingenieros de la ciudad de Loja periodo 2014 - Taday León, Rosa Emilia (2015)
The research topic. THE PARENT FAMILIES AND THEIR IMPACT ON THE SOCIAL DEVELOPMENT OF CHILDREN FROM FIRST YEAR OF BASIC EDUCATION SCHOOL JOSE ENGINEERS Loja PERIOD 2014 has been approached from a scientific point of view, in order to give a contribution to the knowledge of the socio actually in the city and province of Loja. The overall objective verification that contributed to the problem was: To provide a scientific research on single parents in their structure and knowledge in school Jose Engineers and thus strengthen the social development of children who attend this school. For the present research work was the methodology used scientific method, Descriptive, analytic Synthetic, inductive, deductive and Statistical. Which allowed to know the reality of the problem, determine the theoretical foundation. The population studied was 16 children, 16 parents of families and 3 teachers. The technique used was direct observation carried children, the instruments used were: A survey psychology teachers and Assessment of family relationships aimed at parents. The research concludes with a series of important conclusions one concludes that those of the 16 parents applied 9 which corresponds to 56 % , are dysfunctional families; result manifested that refers to a type of family conflict or conflicts that happen that make it not functional.